IMPLEMENTATION OF THE REGENT REGULATION NUMBER 79 OF 2018 CONCERNING THE MANAGEMENT OF VILLAGE OWNED ENTERPRISES - Aisy, Dalia Syareatul; Purnamasari, Irma; Apriliani, Afmi; Seran, Gotfridus Goris; Pratidina, Ginung; Maruapey, Muhammad Husein; Sudarsa, Agus Suarman; Mulyono, Imam Edy (Jurnal Governansi, 2024)
The implementation of the Village Owned Enterprises (BUMDes) policy is the process of implementing and implementing the rules and guidelines that have been set by the government to establish and manage businesses at the village level. This research aims to find out how the Implementation of the Bogor Regent Regulation Policy Number 79 of 2018 in the Management of Village Owned Enterprises (BUMDes), to find out what obstacles are faced in the management of Village-Owned Enterprises (BUMDes), to find out what efforts are made to achieve the policy in Cigombong district, Bogor Regency. This study uses a quantitative method with a descriptive approach with data collection techniques using observations that become the main and secondary data, interviews, questionnaires equipped with documentation data and literature studies as secondary data. The analysis technique used Likert scale measurements and used the Weight Mean Score (WMS) formula. The results of the study received an average score of 3.68 which is included in the good category. This is observed according to aspects such as communication, resources, disposition, and bureaucratic structure that have been well realized, but improvements are needed in several aspects of communication and resources to maximize policy implementation. As a result, the efforts made include training for managers, the need to strengthen communication between the village government and the community, increase and improve human resources and improve the bureaucratic structure that supports BUMDes operations.